Short-term vs. overnight insemination: which one is better for patients with only one or two oocytes retrieved in IVF cycles? - Chen, Jinghua; Liu, Zhenfang; Cai, Jiali; Jiang, Xiaoming; Pan, Luxiang; Zhou, Liying; Chen, Kaijie; Yang, Xiaolian; Chen, Yurong; Liu, Lanlan; Ren, Jianzhi (Frontiers in Endocrinology, 2026)
BackgroundCompared with overnight insemination, it remains uncertain whether short-term insemination can improve outcomes in poor responders, and few studies have used cumulative live birth rate as the primary endpoint. The study aims to compare the effects of short-term insemination and overnight insemination on poor responders with one or two oocytes by evaluating cumulative live births.MethodsA retrospective study was conducted on 2,392 cycles, which were divided into the short-term insemination group (5 h) and the overnight insemination group (17 h) based on gametes’ incubation time. Basic characteristics and clinical outcomes were compared and analyzed using propensity score matching.ResultsThe short-term insemination group got more normal fertilized embryos than the overnight insemination group (P < 0.05). The cumulative live birth rates between the two groups were similar before matching (21.1% vs. 17.6%, P > 0.05) and after matching (20.7% vs 17.9%, P > 0.05). Multivariate logistic regression analysis confirmed that short-term insemination had no adverse effect on the cumulative live birth rate (CLBR). However, in the subgroup of patients who underwent extended culture of all embryos, comparing overnight to short-term insemination, the odds ratios (ORs) for CLBR were 0.40 (95% CI: 0.18–0.88) in the unmatched cohort and 0.39 (95% CI: 0.18–0.84) in the matched cohort.ConclusionsOur analysis suggests that for IVF cycles with a limited oocyte yield (1–2), short-term insemination does not adversely affect the CLBR. Furthermore, it may demonstrate a potential benefit for the subset of patients whose clinical pathway involves the extended culture of all embryos to the blastocyst stage.